Candida infections in patients with psoriasis and psoriatic arthritis treated with interleukin‐17 inhibitors and their practical management. (1st July 2017) - Saunte, D.M.; Mrowietz, U.; Puig, L.; Zachariae, C.
Summary: The recognition of the central role of interleukin (IL)‐17A in the pathogenesis of psoriasis has led to the development of several monoclonal antibodies targeting this cytokine or its receptors for therapeutic purposes. IL‐17A also plays an important role in immunological protection against infections, especially those due to Candida spp., as evidenced by findings in patients with genetic defects in IL‐17‐related immune responses. To assess the potential of anti‐IL‐17 treatment to promote Candida infections, here we have systematically reviewed published clinical trials of patients with psoriasis or psoriatic arthritis. Candida infections were reported in 4·0% of patients treated with brodalumab, 1·7% with secukinumab and 3·3% with ixekizumab vs. 0·3%, 2·3% and 0·8% of those assigned to placebo, ustekinumab or etanercept, respectively. Although the incidence of Candida infection was found to be increased by only a small degree during anti‐IL‐17 therapy, patients undergoing such treatment should be monitored for fungal infection and treated as necessary. We propose adoption of the recently updated recommendations for the practical management of Candida infection in patients administered IL‐17 inhibitors.